Medical and dental space planning : a comprehensive guide to design, equipment, and clinical procedures - Malkin, Jain. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
Medical and Dental Space Planning is an indispensable guide to the myriad of details that make a medical or dental practice efficient and productive. The unique needs of more than thirty specialties, as well as primary care, are explained in the context of new technology and the many regulatory and compliance issues influencing design. Concepts are also presented for ambulatory surgical centers, diagnostic imaging, clinical laboratories, breast care clinics, endoscopy centers, community health centers, radiation oncology, and single-specialty and multispecialty group practices and clinics.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Medical offices -- Design and construction; Dental offices -- Design and construction; ARCHITECTURE -- Buildings -- Public, Commercial & Industrial; Dental offices -- Design and construction; Medical offices -- Design and construction; Facility Design and Construction; Electronic books